Are more nickel ions accumulated in the hair of fixed orthodontic patients? - Mostafa Abtahi; Arezoo Jahanbin; Masoud Yaghoubi; Habibollah Esmaily; Hanieh Zare (Wolters Kluwer Medknow Publications, 2013)
Background and Objectives : All elements existing in orthodontic alloys can be released to the oral cavity as corrosion products; therefore, they can accumulate in body tissues after systemic absorption. Among body tissues that can be evaluated for systemic absorption of nickel, in this study we used hair strands, because if nickel is absorbed systematically, it would accumulate in these strands over time. Furthermore, hair sampling is a non-invasive method, so the main aim of this study was the evaluation of nickel ions release into the hair strands of fixed orthodontic patients compared with the control group in a 4-month duration. Materials and Methods: In this clinical trial, the test group included 24 female patients between 12-20 years of age that were going to begin fixed orthodontic treatment. The control group consisted of their sisters in the same age range, who volunteered to participate in this study. Initial hair samples were taken from both groups at the beginning the study and immediately before setting up the fixed appliances in test group. The samples were taken from three different scalp sites including; frontal, vertex, and occipital areas. After 16 weeks, hair samples were taken from approximately the same scalp areas in both the groups. The samples were analyzed by atomic absorption spectrophotometer and data analyzed by Mann-Whitney test. Results: This study showed that there were significant differences in nickel levels before and after study for case (P = 0.004) and control groups (P = 0.012). The mean nickel concentration after four months was 0.382 ± 0.36 μg/g for controls and 0.673 ± 0.38 μg/g for the case group, which was significantly different (P = 0.002). Conclusion: The hair nickel concentrations significantly increased after insertion of fixed orthodontic appliances as compared with the control group.